Evaluation of Official Development Assistance from a Social-Gender Perspective - Tanaka Yumiko (Japanese Journal of Evaluation Studies, 2001)
This paper tries to provide the overall view of the preceding evaluation study undertaken on the Japanese Official Development Assistance (ODA) from a social-gender perspective, in particular through examining the project evaluation of Japan International Cooperation Agency (JICA), which has been one of the major implementing arms of the Japanese ODA. Succeedingly, it proposes the key issues for future analysis and research for the Social-Gender Evaluation Group established under the Japan Evaluation Society.Gender mainstreaming into Japanese ODA has been mandated, among others, under the ODA Charter (1992) and WID Initiative (1995) issued by the government. Monitoring and evaluation of ODA from a gender perspective have been mandated under the ODA Medium Term Plan (1999). The Basic Law for a Gender Equal Society (1999) also defined in its article 7 that a gender-equal society shall be promoted in close collaboration between internal and international efforts to form such a society.JICA has introduced evaluation methods in 1981 and adopted succeedingly OECD/DAC's evaluation concepts and principles. However, gender evaluation has not been undertaken until 1993, when joint evaluation was conducted on CIDA's gender strategies in Bangladesh. JICA has undertaken gender evaluation of its own projects in 1998 in Sri Lanka and poverty and gender evaluation in Nepal and Paraguay in 2000.Despite all the mandates and evaluation exercises, evaluation methods and system from a social-gender perspective have not yet been fully established and institutionalized for Japanese ODA. One of the major tasks of the Social-Gender Evaluation Group should be directed to develop effective evaluation methods and system of Japan's ODA from a social-gender perspective to ensure its equitable and greater impact.